Characterization of proteins in flagellates and growing amebae of Naegleria fowleri. - Woodworth, T W (1982)
Polypeptides of whole-cell extracts of Naegleria fowleri flagellates and growing amebae were resolved by two-dimensional polyacrylamide gel electrophoresis. Autoradiograms of the [35S]methionine-labeled polypeptides of amebae and flagellates were analyzed by two dimensional densitometry to determine whether there were correlations between intracellular concentration of a protein and subunit size or charge. The majority of the polypeptides of amebae and flagellates had molecular sizes in the range of 20 to 60 kilodaltons. The radioactivity per polypeptide species in the size range of 20 to 60 kilodaltons was greater in amebae than in flagellates. The greatest number of polypeptides detected in amebae and flagellates was in the isoelectric focusing range of pH 6 to 7. The radioactivity per polypeptide species in the isoelectric focusing gradient below 6.3 was greater in amebae than in flagellates. Polypeptides in the size range of 20 to 60 kilodaltons had a median isoelectric point below pI 6.3, whereas those larger than 60 kilodaltons had a median pI value above 6.3. These data indicated that molecular size and charge were not entirely independent variables and that the size and charge of a polypeptide might have an important influence in determining its intracellular concentration in both amebae and flagellates. Autoradiograms were also compared so that changes in intracellular protein complement and concentrations occurring during differentiation could be recognized. The relative amounts of a limited number of polypeptides increased markedly, and others decreased markedly, during enflagellation.